Estudos dos elementos cinematográfico-videográficos na tradução audiovisual para a Libras - Barros, Gracy Kelly Amaral (2023)
This dissertation is a general object analyzed as aesthetic relationships between the elements of cinematographic-videographic language (LCV) and the audiovisual translation and interpretation for Libraries (TIALS) of four audiovisual performances of the poem genre presented at the Mostra Literatura Paraná (2021). Having interdisciplinary theoreticalmethodological support between Sign Language Translation Studies (Nascimento, Nogueira, 2019; Nascimento, Fornari, Segala, 2019; Medeiros, Fernandes, 2020; Nascimento, 2021; Medeiros, 2018; 2021), studies Cinematographic Language (Martin; 2013; Mascelli, 2010; Aumont et al, 2012) and Videographic Language (Dubois, 2004). To visualize the proposed object, the selected videos will contain the following VCL elements analyzed descriptively: layout of the courts; aesthetic movement between translators and camera(s); signal angles; framing; dress and lighting. The Analyzes justify the Aesthetic Elements of the LCV Based on the Theoretical Reference of the Cinematographic-Videographic Field and Compare with the Brazilian Regulatory Standard (NBR) of the Brazilian Association of Standards and Techniques (ABNT) nº 15290/05 Accessible Visuals of the Ministry of Communications (Naves et al., 2016). However, we must note that the elements of the VCL can be used aesthetically by TIALS where we have the opportunity to experience artistic creations in a visual and innovative way, without including audiovisual material, without translating verbal text. In this way, this dissertation seeks to contribute to the work of translators, producers of cultural projects, audiovisual producers and editors, presenting TIALS as an aesthetic, dialogical process integrated into the LCV, sending a discussion to complement the TIALS guidelines especially in artistic contexts.